Dimer-mediated cation diffusion in the stoichiometric ionic conductor Li3N. Issue 7 (1st February 2016) - Mulliner, Alexander D.; Battle, Peter D.; David, William I. F.; Refson, Keith
Abstract : Non-equilibrium molecular dynamics has identified the different diffusion mechanisms that operate in Li3 N and elucidated the key role played by transient Li2 dimers. Abstract : Non-equilibrium molecular dynamics has been used to model cation diffusion in stoichiometric Li3 N over the temperature range 50 < T /K < 800. The resulting diffusion coefficients are in excellent agreement with the available experimental data. We present a detailed atomistic account of the diffusion process. Contrary to the conclusions drawn from previous studies, our calculations show that it is unnecessary to invoke the presence of a small concentration of intrinsic defects in order to initiate diffusion. The structure can be considered to consist of alternating layers of composition Li2 N and Li. As the temperature increases an increasing number of cations leave the Li2 N layers and migrate either to the interlayer space or to the Li layer. Those that move into the interlayer space form Li2 dimers with cations in the Li2 N layers and those that move into the neighboring layer form dimers with cations therein. The two types of dimer are aligned parallel and perpendicular to [001], respectively and have lifetimes of ∼3 ps. The vacancies so created facilitate rapid diffusion in the Li2 N layers and the interlayer cation motion results in slower diffusion perpendicular to the layers.